Evaluation of Ovarian Stimulation Initiated From the Late Follicular Phase Using Human Menopausal Gonadotropin Alone in Normal-Ovulatory Women for Treatment of Infertility: A Retrospective Cohort Study - Zhu, Xiuxian; Fu, Yonglun (Frontiers in Endocrinology, 2019)
Objective: To investigate the feasibility of ovarian stimulation initiated in the late follicular phase using human menopausal gonadotropin (hMG) alone in ovulatory patients undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatments by comparison with that of the short gonadotropin-releasing hormone agonist (GnRH-a) protocol in terms of ovarian response, embryological characteristics, and pregnancy outcomes following frozen-thawed embryo transfer (FET) cycles. Design: Retrospective cohort study Setting: A university-affiliated tertiary hospital Patients: 135 infertile women undergoing their first IVF/ICSI treatment with the freeze-all strategy Interventions: In the study group, ovarian stimulation was initiated in the late follicular phase using hMG alone, with the confirmation of dominant follicular diameter ≥14 mm, while a short GnRH-a protocol was adopted in the control group. Oocyte maturation was induced by human chorionic gonadotropin in both groups. All good quality embryos were cryopreserved for later transfer. Main Outcome Measures: The primary outcome was the incidence of premature luteinizing hormone (LH) surge. Secondary outcomes were the number of mature oocytes retrieved, good-quality embryo rate per oocyte retrieved, and clinical pregnancy rate following FET cycles. Results: No premature LH surge was detected during ovarian stimulation in the study group. There was no statistically significant difference in the number of mature oocytes between the two groups (10±5.6 in the study group versus 8.51±5.03 in the control group, P=0.11). Good-quality embryo rate per oocyte retrieved did not differ between the two groups: 40.18% (313/779) versus 36.67% (253/690), P=0.167. Clinical pregnancy rate per transfer following FET was comparable between the two groups (61.33% versus 52.5%, P=0.267). Conclusion(s): Our study shows that ovarian stimulation initiated in the late follicular phase using hMG alone may be a feasible alternative for normal-ovulatory women undergoing IVF/ICSI treatment with the freeze-all strategy.